IMPLEMENTASI AMERICAN SERVICE DAN PENGARUHNYA TERHADAP KEPUASAN TAMU PEPITO RESTAURANT DI MANADO QUALITY HOTEL - Bet El Lagarense; Sony Wijanarko (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2023)
Implementation of American Service and Its Impact on Pepito Restaurant Guest Satisfaction at Manado Quality Hotel. The aims of this study were to measure, analyze, and explain the effect of American Service implementation on Pepito Restaurant guest satisfaction at Manado Quality Hotel. This research used observation, survey and interview techniques. The sampling method applied was random sampling and the method of analysis used was simple linear regression analysis where variable X (American Service) and variable Y (Guest Satisfaction) with the equation Y'=a+bX and analysis of the correlation coefficient to calculate how strong the relationship between variables X and variables Y. The final results of this study after analyzing the simple linear regression was an equation where Y' = 5.24 + 0.92X indicating that every one-time increase in the American Service (variable X) will cause a change in the increase in the variable Y( guest satisfaction ) as much as 0.92 vice versa. The correlation coefficient (r) = 0.71 and close to 1 means that there is a strong positive influence between the variable X (American Service) on the variable Y (guest satisfaction) and for the determinant coefficient (r2) of 50.80% indicating that there is an influence on the implementation of American service on guest satisfaction and 49.20% is a variable change caused by a lack of good work coordination between waiters/waitresses.